American Taliban a novel - Abraham, Pearl 1960- (New York Random House, 2010)
John's world is wide open to new ideas, philosophies, and religions. Through online chat rooms he meets a young woman who spurs his interest in Islam and Arab literature, and embraces the experience heart, body and soul-- with unforeseen consequences.
Keywords: Muslim converts -- Fiction; Americans -- Pakistan -- Fiction; Americans -- Afghanistan -- Fiction